The haunting. Book 1 - Philbrick, W. R. (W. Rodman); Harnett, Lynn.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1995)
After a shy and rather withdrawn eight-year-old begins receiving frightening supernatural images and messages, he learns about a family legacy which could be considered a curse or a rare gift.
"An Apple paperback" -- T.p.
Keywords: Paranormal fiction